PENGARUH KECERDASAN EMOSIONAL DAN BUDAYA ORGANISASIONAL TERHADAP KINERJA GURU MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada SMP Negeri 2 Sumbergempol Kabupaten Tulungagung) - Sawal Sartono; Gautama Sastra Waskita; Dyan Arintowati; Retnaningsih (Universitas Tulungagung, 2023)
This study aims to determine the Effect of Emotional Intelligence and Organizational Culture on Teacher Performance Through Job Satisfaction as Intervening Variables at SMP Negeri 2 Sumbergempol, Tulungagung Regency. To manage HR efficiently and effectively, organizations must pay attention to each individual through human resource management. The organization ensures the effective and efficient use of human talent to achieve organizational goals. This research is an explanatory research. This research was conducted at SMP Negeri 2 Sumbergempol, Tulungagung Regency. The population in this study were teachers and staff at SMP Negeri 2 Sumbergempol Tulungagung. The sampling method used is purposive sampling. The results showed that emotional intelligence had a positive and significant effect on employee performance at SMP Negeri 2 Sumbergempol Tulungagung. Organizational culture has a positive and significant effect on employee performance at SMP Negeri 2 Sumbergempol Tulungagung. Emotional intelligence on employee performance through job satisfaction at SMP Negeri 2 Sumbergempol Tulungagung. Organizational culture on employee performance through job satisfaction at SMP Negeri 2 Sumbergempol Tulungagung. Keywords: teacher performance, emotional intelligence and organizational culture, job satisfaction